Hydration-Shell Solvation and Screening Govern Alkali Cation Concentrations at Electrochemical Interfaces - Tran, Bolton; Janik, Michael J.; Milner, Scott T. (Journal of physical chemistry. C, 2024)
Knowledge of the concentration of alkali cations in an electrochemical double layer is essential for interpreting and leveraging cation effects in electrocatalysis. We systematically study the concentration profiles of four alkali cations (Li+, Na+, K+, and Cs+) at a Ag(111)-aqueous interface. Using classical molecular dynamics, the potential of mean force (PMF) of cations approaching a metal surface was computed and decomposed into contributions from the solvent and the metal surface. We find that hydration shell deformations contribute importantly to the free energy of cations near the electrode. Cations with larger ionic radii and looser hydration shells experience less solvation loss and less short-range Coulombic screening, which enable them to adsorb more strongly to a negatively charged surface (Cs+ > K+ > Na+ > Li+). We compute the non-Faradaic electrosorption valency and the interfacial capacitance and show that these experimentally relevant quantities encode the relative concentration of the adsorbed alkali cations of different sizes, but not the spatial positions of cations in the double layer.